ABOUT METAPHORS - Kobiljonova, Shukronahon; Gaziyeva, M (International Conference on Science, Education & Law, 2026)
This article examines the theoretical foundations of metaphor and analyzes the specific features of synesthetic metaphor as one of its distinctive types. Synesthetic metaphor is interpreted as a stylistic device that arises from the transfer of perceptions between different sensory modalities. The article highlights its role in linguistics and literary studies, as well as its semantic and stylistic characteristics, supported by relevant examples. Furthermore, the study reveals the function of synesthetic metaphor in enhancing imagery and its aesthetic impact in speech.